Impact of minimal invasive extracorporeal circulation on the need of red blood cell transfusion. (October 2019) - Ellam, Sten; Pitkänen, Otto; Lahtinen, Pasi; Musialowicz, Tadeusz; Hippeläinen, Mikko; Hartikainen, Juha; Halonen, Jari
Objective: Minimal invasive extracorporeal circulation may decrease the need of packed red blood cell transfusions and reduce hemodilution during cardiopulmonary bypass. However, more data are needed on the effects of minimal invasive extracorporeal circulation in more complex cardiac procedures. We compared minimal invasive extracorporeal circulation and conventional extracorporeal circulation methods of cardiopulmonary bypass. Methods: A total of 424 patients in the minimal invasive extracorporeal circulation group and 844 patients in the conventional extracorporeal circulation group undergoing coronary artery bypass grafting and more complex cardiac surgery were evaluated. Age, sex, type of surgery, and duration of perfusion were used as matching criteria. Hemoglobin <80 g/L was used as red blood cell transfusion trigger. The primary endpoint was the use of red blood cells during the day of operation and the five postoperative days. Secondary endpoints were hemodilution (hemoglobin drop after the onset of perfusion) and postoperative bleeding from the chest tubes during the first 12 hours after the operation. Results: Red blood cell transfusions were needed less often in the minimal invasive extracorporeal circulation group compared to the conventional extracorporeal circulation group (26.4% vs. 33.4%, p = 0.011, odds ratio 0.72, 95% confidence interval 0.55-0.93), especially in coronary artery bypass grafting subgroup (21.3% vs. 35.1%, p < 0.001, odds ratio 0.50, 95% confidence interval 0.35-0.73). Hemoglobin drop after onset of perfusion was also lower in the minimal invasive extracorporeal circulation group than in the conventional extracorporeal circulation group (24.2 ± 8.5% vs. 32.6 ± 12.6%, p < 0.001). Postoperative bleeding from the chest tube did not differ between the groups (p = 0.808). Conclusion: Minimal invasive extracorporeal circulation reduced the need of red blood cell transfusions and hemoglobin drop when compared to the conventional extracorporeal circulation group. This may have implications when choosing the perfusion method in cardiac surgery.